Notational analysis of female´s singles badminton matches in Olympic Games in Beijing - Torres-Luque, G.; Peralvarez, E.; Cabello-Manrique, D.; Femia, P.; Urena, A. (Proceedings book of the 14th ITTF Sports Science Congress & the 5th World Racquet Sports Congress, Suzhou, May 23.-25. 2015, 2017)
The aim of this study was to determine the gestural structure of female´s singles badminton matches in Olympic Games. 36 single´s badminton matches in Olympic Games were selected (76.59% of total matches in competition). Nine matches were deleted (two withdrawal, seven for more than 20 points of different). Matches were played with the current "rally point scoring" system, where the one who wins the best of 3 games of 21 points is the winner. Given the category of the tournament, all participants were the best players in the world at that time. Official videos recorded by the organizations of the Beijing 2008 Olympic Games were used to carry out the analysis of the matches. Matches were analysed with Kinovea 8.15 software and analysis of all games was done following the methods of Anguera (2003). For gestural structure the classification proposed by Spanish Badminton Federation was taken as a reference, although badminton strokes were grouped into seven categories because of simplifying: a) underhand; b) under back; c) half hand; d) half back; e) high hand; f) high back; g) high rectified. The results had shown a total of 17225 strokes analysed. In turn, strokes volumes were: a) 3362 (19.6%); b) 3469 (20.1); c) 1570 (9%); d) 961 (5.5%); e) 5472 (31.8%); f) 191 (1.2%); g) 2200 (12.7%). No studies so far have analysed gestural characteristics of elite badminton, a sport whose practice has spectacularly increased over the last few years. These studies are necessary for the planning and specific training female badminton.